Genetic characterization of mango (Mangifera indica L.) cultivars through isozyme analysis - Coroza-Almontero, Cecilia; Espino, Rene Rafael C. (2010)
Thirty-four mango cultivars were characterized electrophoretically using starch gel electrophoresis. Nine enzyme systems showed polymorphism. These include phosphoglucoisomerase (PGI), shikimate dehydrogenase (SDH), isocitrate dehydrogenase (IDH), esterase (EST), malate dehydrogenase (MDH), acid phosphatase (ACP), phosphoglucomutase (PGM), glucose-6-phosphatedehydrogenase (G-6-PD) and malic enzyme (MAL). A total of 13 presumptive loci were detected for the nine enzymes investigated: one for SDH, IDH, MDH, G-6-PD and MAL, two for PGI, EST, ACP and PGM. The most useful for cultivar identification were the PGI and PGM isozymes. 'Dingras' could be differentiated from the other varieties by its isozyme banding pattern for PGI, while 'Carabao' accessions ('GES 84', 'Lamao' and 'Talaban') exhibited a unique banding pattern for the enzyme PGM. These banding patterns may be used for cultivar identification.
Keywords: Mango; Genetic polymorphisms